Technology parks as real estate undertakings in Latin America - Torres, Stephanie; Alves, Silvana; Vidal, Francisco (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
Technology parks are real estate spaces that articulate activities between government, academia and enterprises to promote not only spreading of knowledge but also regional and national competitiveness by supplying new processes, products and services. Despite the great deal of discussion about such parks, there are still very few studies that deal with analyzing them within the context of Latin America. Thus, a multiple case study was conducted to analyze and compare qualitatively eight parks in that geographical region. Based on the concept of innovation habitats, key conditioning points were identified that are incorporated into the property management of the parks. The study presented the macro- and microenvironments that influence the sustainability of those initiatives, which allowed formulating recommendations to make cooperation and integration of those key points viable in actual technology generation and transfer by Latin American parks.